A ROP GTPase signaling pathway controls cortical microtubule ordering and cell expansion in Arabidopsis - Fu, Ying (2009)
Cortical microtubules (MTs) participate in the spatial control of cell expansion and division that is required for plant growth and morphogenesis. Well-ordered transverse cortical MTs promote cell elongation and restrict radial cell expansion. The molecular mechanism controlling their ordering is poorly understood. We report the first known signaling pathway that promotes the organization of cortical MTs into parallel arrays oriented perpendicular to the axis of cell elongation in plants. Well-ordered MTs locally restrict cell expansion to promote indentation formation in the jigsaw puzzle-shaped pavement cells of Arabidopsis leaves. Deleting ROP6, a Rho-family GTPase, randomized cortical MTs and released the localized restriction of cell expansion, whereas ROP6 overexpression enhanced MT ordering, turning the jigsaw puzzle appearance of cells into a cylindrical shape. ROP6 directly binds and activates MT-associated RIC1 to achieve the MT ordering. The ROP6-RIC1 pathway also affects MT ordering of hypocotyl cells, showing a broad role for this pathway in the spatial regulation of cell expansion.